Introduction to the Special Issue - Patsy Moskal; Laurie Dringus (Online Learning, 2023)
Every year, the Online Learning Consortium holds two flagship conferences: OLC Accelerate, held in the fall, and OLC Innovate, held jointly with MERLOT each spring. This past year, OLC Accelerate 2022, was held virtually November 1-2, 2022 and live, in Orlando, Florida, November 14-17, 2022. OLC Innovate 2023, was held virtually April 4-6, 2023 and live in Nashville, Tennessee, April 18-21, 2023.